The anterior eye and therapeutics : - Stapleton, Fiona (Oxford University Press, 2003)
This invaluable text for anyone interested in the eye and contact lens wear presents a concise, up-to-date review of the anterior eye and therapeutics, a subject with far reaching implications for future practice. Balanced, critical content presents the very latest information in a highly readable format so readers can find specific information quickly. In addition to the necessary basic science, it offers sound, clinical advice and evidence-based research findings. Superb illustrations clarify visual concepts and help readers apply knowledge to optometry practice.